Intrathecal inflammation precedes development of Alzheimer's disease. Issue 9 (21st August 2003) - Tarkowski, E; Andreasen, N; Tarkowski, A; Blennow, K
Abstract : Objectives: To analyse the cerebrospinal fluid (CSF) values of the proinflammatory cytokines, interleukin 1β (IL1β), tumour necrosis factor α (TNFα), GM-CSF, of the anti-inflammatory cytokine TGFβ, of tau protein, a marker for neurodegeneration, and of β amyloid (Aβ), a protein involved in the formation of senile plaques, in prospectively followed up patients with mild cognitive impairment (MCI). Methods: Analyses of CSF levels of TNFα, IL1β, GM-CSF, TGFβ, βa, and tau protein were performed using ELISA in 56 patients with MCI who were followed up prospectively and in 25 age matched, healthy controls. Results: Patients with MCI displayed significantly higher levels of TNFα and tau protein and significantly lower levels of TGFβ and Aβ compared with the healthy controls. After nine months of follow up, 25 patients still displayed MCI while the remaining 31 patients had progressed to Alzheimer's disease (AD). Only MCI patients who progressed to AD at follow up, showed significantly higher CSF levels of TNFα than controls. In addition, reduced CSF-Aβ42 levels were only found in MCI patients that progressed to AD, further supporting the notion that disturbed metabolism of Aβ is an early finding in AD. Conclusions: These results demonstrate increased production of the proinflammatory cytokine, TNFα and decreased production of the anti-inflammatory cytokine TGFβ in patients with MCI at risk to develop AD, suggesting a propensity towards inflammation in this patient group and indicating that CNS inflammation is a early hallmark in the pathogenesis of AD.